Modelling Export Activity of Eleven APEC Countries - Matyas, L.; Konya, L.; Harris, Mark (2004)
The gravity model has long been used for modelling and predicting trade flows. This paper generalises the gravity model allowing for proper representation of local and target country effects and also the business cycle. The new approach is based on a panel data framework (instead of a simple cross sectional or time series approach) where the additional information available from using both types of data (i.e. cross sectional and time series) is utilised to properly model all the specific effects. The model is applied to a panel of APEC countries.